EFFECTS OF FEEDING STRATEGIES AND SUPPLEMENTAL LIPOTROPIC FACTORS ON GROWTH PERFORMANCE, ASCITES-RELATED INDICES, SERUM METABOLITES AND MEAT QUALITY IN BROILER CHICKENS REARED AT HIGH ALTITUDE - V. Rezaeipour1; F. Aghayar; A. Bozorgnia; M. Norozi; H. Zakaria (Journal of Animal and Plant Sciences, 2019)
The aim of the study was to investigate the effects of feeding programs in combination with supplemental lipotropic agents on performance, ascites-related indices, blood metabolites and breast meat quality in broiler chickens reared at high altitude (2,200 m above sea). A total of 450 day-old Ross broiler chickens were randomly assigned to 6 treatments with 5 pens of 15 birds per each. The experiment was carried out in a completely randomized design with 2 × 3 factorial arrangement, including two feeding program (ad libitum or early feed restriction) and three status of lipotropic supplementations (a control diet, 150 mg/kg carnitine as L-carnitine, and 1,000 mg/kg choline as choline chloride). The results showed that dietary supplementation with carnitine improved body weight gain and feed conversion ratio (FCR) in broilers (P≤ 0.05). The relative weight of the heart was lower in broilers fed choline supplemented diet compared with control group (P≤ 0.05). Feeding broiler chickens with carnitine increased the serum concentration of glucose (P≤ 0.05). However, supplementation of the diet with carnitine reduced serum concentration of triglycerides (P≤0.05). Supplemental carnitine reduced the susceptibility of the meat (thiobarbituric acid number) to lipid peroxidation (P≤ 0.05). The ascites-related indices, including the weight of right ventricle (RV) and the ratio of right-to-total ventricular weight were lower in broilers which received carnitine and choline supplementation which reared under early feed restriction (P≤ 0.05). In conclusion, supplemental carnitine improved growth performance, ascites-related indices and meat quality of broilers. Besides, early feed restriction improved ascites-related indices in broiler chickens reared at high altitude.
Keywords: altitude; broilers; ascites; lipotropic agents; liver health.